Pengaruh Disiplin dan Kepuasan Kerja terhadap Motivasi Kerja dan Dampaknya pada Kinerja Pegawai Satuan Polisi Pamong Praja dan Pemadam Kebakaran Kabupaten Tanjung Jabung Timur - Zulfaisyal, Zulfaisyal; Bukit, Pantun; Akbar, Ali (Universitas Batanghari, 2025)
The purpose of this study is to analyze the influence of discipline and job satisfaction on work motivation and its impact on the performance of Civil Service Police Unit and Fire Department employees of Tanjung Jabung Timur Regency. The method used in this study is a descriptive verification and quantitative method. The object of research in this study is the influence of discipline and job satisfaction on work motivation and its impact on the performance of employees of the Civil Service Police Unit and Fire Department of Tanjung Jabung Timur Regency. Based on the approach, the number of samples can be known, namely 50 people. This study uses the PLS analysis method. The results of the study show that this study shows that there is a positive and significant influence between several factors on work motivation and employee performance at the Satpol PP-Damkar Tanjung Jabung Timur Regency. Employee discipline contributes 41.8% to increasing work motivation, while job satisfaction has a greater influence, namely 57.8% on work motivation. In addition, employee discipline also affects employee performance by 33.2%, and job satisfaction contributes 36.5% to employee performance. Work motivation itself plays an important role with a positive influence of 30.7% on employee performance. In addition, employee discipline and job satisfaction have been shown to have an indirect influence on employee performance through work motivation, respectively 12.8% and 17.8%.